BRAF V600E analysis for the differentiation of papillary craniopharyngiomas and Rathke's cleft cysts - Schweizer, Leonille; Capper, David; Hölsken, Annett; Fahlbusch, Rudolf; Flitsch, Jörg; Buchfelder, Michael; Herold-Mende, Christel; Deimling, Andreas von; Buslei, Rolf (Neuropathology & applied neurobiology, 2015)
Aims The differential diagnosis of cystic epithelial masses of the sellar region, especially the histopathological differentiation of craniopharyngiomas and Rathke's cleft cysts, poses a challenge even to experienced diagnosticians. Recently, BRAF V600E mutations have been described as a genetic hallmark of papillary craniopharyngiomas. We investigated a series of 33 Rathke's cleft cysts to determine the frequency of BRAF V600E mutations and its suitability as an additional diagnostic marker for the differentiation of cystic lesions of the sellar region. Methods Thirty-three Rathke's cleft cysts and 18 papillary craniopharyngiomas were analysed for BRAF mutational status by immunohistochemistry using a monoclonal antibody (VE1) that selectively recognizes the BRAF V600E mutant epitope and additional BRAF pyrosequencing in a subset of samples. Results Thirty of 33 specimens diagnosed as Rathke's cleft cysts were negative by VE1 immunohistochemistry and pyrosequencing, whereas in three cysts and in all the 18 papillary craniopharyngiomas, a BRAF V600E mutation was detected. Clinical and histological re-evaluation of the three BRAF V600E mutated cases formerly diagnosed as Rathke's cleft cysts revealed unusual presentations. Two of them were rediagnosed as papillary craniopharyngiomas. The patient of the third case had a history of craniopharyngioma operated 14 years before, and reoperation showed a cystic epithelial lesion with unclear histology. Conclusions The determination of BRAF mutational status is recommended in any cystic sellar lesion and can in most cases be provided by VE1 immunohistochemistry even in specimens of low cellularity. Confirmation by (pyro-)sequencing should be attempted whenever sufficient epithelium is available due to variable staining results.